Differentiation of lexical units in languages with different systems according to their linguocultural characteristics - Aida Ismayilova (Abdul Media Literasi, 2026)
This study examines complex lexical units in Azerbaijani and English from linguocultural and cognitive perspectives, aiming to identify differences in their structural organization, semantic composition, and cultural interpretation. Using a qualitative comparative approach, the research analyzes compound words and syntactic expressions from lexicographic sources. The results demonstrate that English lexical units are generally more compact and semantically condensed. Noun-noun compounds, in particular, express culturally embedded meanings in a cognitively economical manner. Conversely, Azerbaijani lexical units expand meaning through syntactic and morphological means, distributing semantic information across several elements and relying more strongly on contextual interpretation. While both languages encode culturally significant knowledge, they employ different cognitive strategies: English favors conceptual compression, whereas Azerbaijani prefers more explicit, descriptive, and relational expressions. Ultimately, the study concludes that these structural differences reflect deeper typological, cultural, and cognitive patterns. This confirms that language structure, cognitive processes, and cultural experience are inextricably linked in the conceptualization and expression of meaning.